[Ni4(OH)3AsO44(B‐α‐PW9O34)4]28−: A New Polyoxometalate Structural Family with Catalytic Hydrogen Evolution Activity. Issue 48 (8th October 2015) - Lv, Hongjin; Chi, Yingnan; van Leusen, Jan; Kögerler, Paul; Chen, Zheyuan; Bacsa, John; Geletii, Yurii V.; Guo, Weiwei; Lian, Tianquan; Hill, Craig L.
Abstract: A new structural polyoxometalate motif, [Ni4 (OH)3 AsO4 4 ( B ‐α‐PW9 O34 )4 ] 28−, which contains the highest nuclearity structurally characterized multi‐nickel‐containing polyanion to date, has been synthesized and characterized by single‐crystal X‐ray diffraction, temperature‐dependent magnetism and several other techniques. The unique central Ni16 (OH)12 O4 (AsO4 )4 core shows dominant ferromagnetic exchange interactions, with maximum χ m T of 69.21 cm 3 K mol −1 at 3.4 K. Significantly, this structurally unprecedented complex is an efficient, water‐compatible, noble‐metal‐free catalyst for H2 production upon visible light irradiation (photosensitizer=[Ir(ppy)2 (dtbbpy)][PF6 ]; sacrificial electron donor=triethylamine or triethanolamine). The highest turnover number of approximately 580, corresponding to a best quantum yield of approximately 4.07 %, is achieved when using triethylamine as electron donor in the presence of water. The mechanism of this photodriven process has been probed by time‐solved luminescence and by static emission quenching. Abstract : Welcome to the family : The multi‐nickel carbon‐free polyoxometalate complex, [Ni4 (OH)3 AsO4 4 ( B ‐α‐PW9 O34 )4 ] 28−, the highest nuclearity structurally characterized multi‐nickel‐containing polyanion developed to date, was synthesized by using a facile, high‐yield, one‐pot method and is an efficient, noble‐metal‐free catalyst for H2 production under visible‐light irradiation.